2016
DOI: 10.1039/c5gc02073e
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of hydrophobic reduced graphene oxide supported Ni-B-P-O and Co-B-P-O catalysts and their high hydrodeoxygenation activities

Abstract: Hydrophobic reduced graphene oxide supported Ni-B-P-O and Co-B-P-O catalysts were beneficial to disperse in the non-polar solvent, prevent the contact with water, and consequently protected the active phases and exhibited high catalytic activity in the liquid-phase p-cresol HDO reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Representing qt values versus time, while a linear pseudo-second-order plot was more suitable for collagen and BSA ( Figure 2 c), a nonlinear pseudo-second-order plot was fit for elastin adsorption ( Figure 2 d) [ 60 ]. Collagen showed a ten-fold higher adsorption rate constant (K 2 ) than BSA and elastin, indicating the highest affinity for rGO than elastin or BSA and due to the strong hydrophobic–hydrophobic interactions between rGO surface and collagen [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Representing qt values versus time, while a linear pseudo-second-order plot was more suitable for collagen and BSA ( Figure 2 c), a nonlinear pseudo-second-order plot was fit for elastin adsorption ( Figure 2 d) [ 60 ]. Collagen showed a ten-fold higher adsorption rate constant (K 2 ) than BSA and elastin, indicating the highest affinity for rGO than elastin or BSA and due to the strong hydrophobic–hydrophobic interactions between rGO surface and collagen [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggested that the composite films had hydrophobicity. For the starter, CNT and Gr are both hydrophobic [32,33] and they are also nanomaterials. When CNT and Gr were used as the fillers, the matrices demonstrated great roughness, thereby reducing their surface energy and achieving a hydrophobic effect similar to that of lotus leaves.…”
Section: Functional Group Reaction Analysis By Ftirmentioning
confidence: 99%
“…[11] To circumvent the problem of partial oxidationo fa ctive sites, it was demonstrated that water-sensitivea ctive sites could be protected against deactivation during HDO by adjustment of the catalyst's surface polarity. [12,13] Ta iloring the surface polarity has been demonstrated to exert as ignificant impact on the catalytic performancef or a varietyofreactions. [14] Notably,the adjustment of surface polarity can have ac rucial influence on activity and selectivityf or oxidation reactions of organic compounds using peroxides.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional metal sulfide catalysts are known to suffer from deactivation during HDO in the presence of water by partial oxidation of the nickel sulfide phase . To circumvent the problem of partial oxidation of active sites, it was demonstrated that water‐sensitive active sites could be protected against deactivation during HDO by adjustment of the catalyst's surface polarity …”
Section: Introductionmentioning
confidence: 99%